Crystal Structure Determination of Coordination Polymers Using Combined Computational Simulation and Powder XRD Analysis - Kim, SungChul; Lee, Byeong hyeon; Junho Ha; Bae, Minsung; Won, Sung Ok (9th International Symposium on Practical Surface Analysis (PSA-24), 2024)
In this study, we introduced an enhanced approach combining computational simulations and powder X-ray diffraction (XRD) analysis to accurately determine the crystal structures of coordination polymers, which are challenging to crystallize as single crystals. Since X-rays primarily interact with electrons, the inherent weak diffraction signal from the organic components complicates XRD analysis. Furthermore, the presence of thermal vibrations in ligands and low crystallographic symmetry results in complex diffraction patterns, making initial structure modeling particularly difficult. To address these challenges, computational simulations were employed to predict the thermodynamically stable positions of atom clusters, which served as the initial models for XRD analysis. The rigid body method and simulated annealing techniques were then applied to refine the atomic positions. Finally, Rietveld refinement was performed to obtain the final crystal structure, which was subsequently validated for structural stability using molecular dynamics calculations. This integrated analytical approach holds significant potential for advancing the structural analysis of various coordination polymers.